SUSTAINABLE DEVELOPMENT OF CENTRAL AND PERIPHERAL REGIONS OF SLOVAKIA - VITÁLIŠOVÁ, Katarína; BORSEKOVÁ, Kamila; LISHCHYNSKYY, Ihor; LYZUN, Mariia (Journal of European Economy, 2022)
Aspects of regional and local sustainable development are turning into key elements of strategic planning documents in EU countries. The topic of sustainable development includes issues of both urban and peripheral areas. It encompasses the classic fields of environmental protection and green energy, as well as the parameters of social inclusion, creative capital development, community and neighbourhood building, etc. The paper reviews the implementation of sustainable development goals in Slovakia with a focus on the programme promoting green infrastructure and the practice of mixed-use urban spaces. The principles of green infrastructure are introduced in Slovakia in line with the concepts of NECONET ecological networks and ÚSES systems of territorial environmental sustainability. The 2030 Environmental Strategy of Slovakia covers three areas, namely water protection and biodiversity, climate change and air protection, and green economy. Prominence is given to the development of renewable energy in the country. The paper determines the main obstacles to the development of Slovakian green infrastructure compared to that of the EU. These include a lack of financing, slow adoption of legislation, and lack of regulation in the land ownership rights. JEL: Q01, R10, R58.